2011
DOI: 10.1287/opre.1110.0912
|View full text |Cite
|
Sign up to set email alerts
|

Structured Replacement Policies for Components with Complex Degradation Processes and Dedicated Sensors

Abstract: Failure of many engineering systems usually results from a gradual and irreversible accumulation of damage, a degradation process. Most degradation processes can be monitored using sensor technology. The resulting degradation signals are usually correlated with the degradation process. A system is considered to have failed once its degradation signal reaches a prespecified failure threshold. This paper considers a replacement problem for components whose degradation process can be monitored using dedicated sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(64 citation statements)
references
References 47 publications
0
64
0
Order By: Relevance
“…In the condition-based maintenance literature, there has been a long and rich history of establishing structural properties of optimal maintenance policies (see, e.g., Ross 1971, Makis and Jardine 1992, White 1978, Elwany et al 2011, Maillart 2006, Kurt and Kharoufeh 2010, Ulukus et al 2012. Although a lot of research has been conducted in this area, to our knowledge, this paper constitutes the first paper reporting structural results for maintenance optimization in the presence of model miss-specification.…”
Section: Introductionmentioning
confidence: 99%
“…In the condition-based maintenance literature, there has been a long and rich history of establishing structural properties of optimal maintenance policies (see, e.g., Ross 1971, Makis and Jardine 1992, White 1978, Elwany et al 2011, Maillart 2006, Kurt and Kharoufeh 2010, Ulukus et al 2012. Although a lot of research has been conducted in this area, to our knowledge, this paper constitutes the first paper reporting structural results for maintenance optimization in the presence of model miss-specification.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to have a cost-saving and a better generalization capability than conventional constant control-limit policy. The studies about dynamic control-limit policy can be classified mainly into three categories, such as inspection rate-dependent threshold [5], age-dependent threshold [4,8,15] and degradation-dependent threshold [26]. For an inspection rate-dependent threshold [5], the higher the inspection rate, the higher the degradation-type PM threshold.…”
Section: Introductionmentioning
confidence: 99%
“…For an age-dependent threshold, PM threshold decreases in age and should be triggered by smaller signal values when it deteriorates [4]. The PM threshold can also be non-decreasing in age and it can be more tolerant of larger signal values for older systems, if there is increasing accuracy in predicting the future signal value [8]. For a degradation-dependent threshold, Zhao et al [26] proposed an adaptive maintenance decision to take into account the state of covariates to dynamically adapt the PM threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Some successful examples of implementing CBM in real systems have demonstrated its efficiency and effectiveness in preventing catastrophic failures and improving maintenance performance (e.g. [1,4,6,11,12,14]). …”
Section: Introductionmentioning
confidence: 99%
“…The degrading system was modeled by a gamma process, and multiple control limits were used to determine the current maintenance actions and future inspection times. Elwanly et al [6] analyzed a replacement problem for the exponentially increasing degradation system. They sciENcE aNd tEchNology demonstrated that the optimal replacement policy was a multi-level control-limit policy with monotonically increasing control limits.…”
Section: Introductionmentioning
confidence: 99%